PENYULUHAN PENTINGNYA PERANAN KELUARGA TERHADAP PENGEMBANGAN MINAT BERWIRAUSAHA EKONOMI DAN BISNIS ISLAM DALAM DIRI SEORANG ANAK - Siti Aliah; Rully Trihantana; Ermi Suryani (Jurnal Pengabdian Kepada Masyarakat Manajemen Bisnis Syariah: Program Studi Manajemen Bisnis Syariah, 2021)
Abstract As a Muslim, entrepreneurship is one part of one's efforts in carrying out worship to seek the pleasure of Allah SWT, not only seeking luck in worldly life but also luck in the hereafter. This paper aims to explore more deeply about the role of the family as an important part in growing and developing one's talents and interests in entrepreneurship naturally and is studied in a literature review. The success of an entrepreneurship is certainly not easy, and requires a distinctive character and motive in entrepreneurship, parents who have entered the world of entrepreneurship can naturally influence someone in preparing themselves as entrepreneurs by getting an entrepreneurial education environment from their parents. Keywords: Natural Resources, Human Resources, Entrepreneurship